2013
DOI: 10.1080/17501229.2013.836205
|View full text |Cite
|
Sign up to set email alerts
|

Forming a clearer image of the ideal L2 self: the L2 Motivational Self System and learner autonomy in a Japanese EFL context

Abstract: Research on the L2 Motivational Self System has drawn considerable attention in Second Language Acquisition. Previous studies have discussed the system itself, its basic concepts and their relationships to such affective variables as anxiety in various L2 learning contexts. The findings of these studies suggest that (1) having a clearer image of one's ideal L2 self might facilitate motivated L2 learning behaviour, (2) affective variables can promote or hinder learners' will to envision their ideal L2 selves, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 31 publications
6
33
3
Order By: Relevance
“…Therefore, the role of family cannot be neglected. Although Ueki and Takeuchi (2013) indicated that others' influence was a predictor of the ought-to L2 self, the present study specifically revealed family influence to be the predictor of not only the OLS but also the ILS and LLE.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…Therefore, the role of family cannot be neglected. Although Ueki and Takeuchi (2013) indicated that others' influence was a predictor of the ought-to L2 self, the present study specifically revealed family influence to be the predictor of not only the OLS but also the ILS and LLE.…”
Section: Discussioncontrasting
confidence: 92%
“…The strong effect of family influence revealed that all three subcategories of the L2MSS were influenced by the participants' family members. The results somewhat diverged from previous studies (Csizér & Kormos, 2009;Taguchi et al, 2009;Ueki & Takeuchi, 2013). Taguchi et al (2009) considered family influence to be a factor affecting the ought-to L2 self, and Ueki and Takeuchi (2013) considered other people's influence to be the factor contributing to ought-to L2 self.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…(Dörnyei & Chan, 2013, p. 439) The L2 Motivation Self System has been the basis of several studies in Iran, China, Singapore, Japan, South Korea, and Pakistan. Some of the studies aimed to validate the L2 Motivational Self System (e.g., T. Kim & Y. Kim, 2014;Magid, 2014;Papi, 2012;Taguchi et al, 2009;Ueki & Takeuchi, 2013). Other studies examined the role of the ideal L2 self in predicting motivated behavior and English learning achievement, and identified its relationship with learning anxiety, gender, and L3 self (e.g., Csizér & Lukács, 2010;Henry, 2009;Papi, 2010).…”
Section: Introductionmentioning
confidence: 99%